Suicidal ideation, anxiety, and depression in patients with multiple sclerosis - Carlos Bernardo Tauil; Talyta Cortez Grippe; Ronaldo Maciel Dias; Rafael Paternò Castello Dias-Carneiro; Narel Moita Carneiro; Ana Carolina Rodrigues Aguilar; Flávia Martins da Silva; Felipe Bezerra; Leonardo Kenzo de Almeida; Vitoria Lana Massarente; Elaine de Carvalho Giovannelli; Charles Peter Tilbery; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Psychiatric disorders frequently occur in patients with multiple sclerosis (MS); however, limited reports are available on these comorbidities. We aimed to investigate the relationships among MS, anxiety, depression, and suicidal ideation. Methods: One hundred and thirty two patients with relapsing-remitting MS were evaluated using the Expanded Disability Status Scale, Beck Depression Inventory-II (BDI-II), Beck Scale for Suicide Ideation (BSI), and Hospital Anxiety and Depression Scale. Results: A hierarchical regression analysis was performed to evaluate the variables. The regression equation significantly predicted the BSI score (R2 = 0.306; adjusted R2 = 0.273; F (9, 125) = 9.18; p < 0.0005), and the BDI-II score was the only variable that contributed significantly to this model (p < 0.0005). Conclusions: A high prevalence of depression and anxiety, and a higher rate of suicidal ideation were identified in MS patients compared to the general population. The presence of depressive symptoms appeared to have a direct influence on the risk of suicide.